Ships in the Port of Buenos Aires in the mid-19th Century: the Potential of The British Packet and Argentine News: A Methodological Essay - Mateo, José; Camarda, Maximiliano; Nieto, Agustín; Caruso, Laura (Ejes de Economía y Sociedad, 2024)
Maritime, and even river and lake navigation, continues to be the most widely used means of world trade. And the ports are the necessary interfaces between the forelands and the hinterlands of the different connected regions. Although this is an age-old activity, in the second half of the nineteenth century it took an exponential boost in what was called the "first globalization". The information became a crucial input for all those involved in the import and export trade, and the press of each port city began to record it day by day in singular detail. This paper is a methodological essay over a short period of time with one of these sources. To do this, we implemented computer tools for data collection and prepared a table with a series of indicators that could be analyzed with this type of source. This similarity is very marked throughout the press of the world. Although we can't offer diachronic results with this cut, its execution does allow us to build the themes and problems, the containers of information, and some instruments that we intend to use in the larger project in which our research is inserted.